2014
DOI: 10.1007/s11071-014-1854-7
|View full text |Cite|
|
Sign up to set email alerts
|

Numerical simulation for two-dimensional variable-order fractional nonlinear cable equation

Abstract: The cable equation plays a central role in many areas of electrophysiology and in modeling neuronal dynamics. This paper reports an accurate spectral collocation method for solving one-and twodimensional variable-order fractional nonlinear cable equations. The proposed method is based on shifted Jacobi collocation procedure in conjunction with the shifted Jacobi operational matrix for variable-order fractional derivatives, described in the sense of Caputo. The main advantage of the proposed method is to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
102
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(102 citation statements)
references
References 57 publications
0
102
0
Order By: Relevance
“…The expressions (21) and (22) can be written using matrix forms of the Jacobi polynomials, respectively, as…”
Section: Fundamental Matrix Relationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expressions (21) and (22) can be written using matrix forms of the Jacobi polynomials, respectively, as…”
Section: Fundamental Matrix Relationsmentioning
confidence: 99%
“…Recently, Bharwy et al [15][16][17][18][19][20][21][22] have used Jacobi polynomials both in operational matrix method and in spectral collocation method for solving some class of fractional differential equations; for instance, nonlinear sub-diffusion equations, delay fractional optimal control problems, time fractional Kdv equations, Caputo fractional diffusion-wave equations, fractional nonlinear cable equation, and fractional differential equations.…”
Section: Introduction Orthogonal Jacobi Polynomialsmentioning
confidence: 99%
“…They can provide suitable mathematical models for describing anomalous diffusion and transport dynamics in complex systems that cannot be modeled accurately by normal integer order equations. Recently, researchers have found that many physical processes exhibit fractional order behavior that varies with time or space for the mathematical modeling of real-world physical problems [1][2][3][4] such as earthquake modeling, traffic flow model with fractional derivatives [5] and financial option pricing problems [6], to name these only.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they proposed a new numerical technique based on a certain two-dimensional extended differential transform via local fractional derivatives and derive its associated basic theorems and properties. Most recently, Bhrawy et al proposed a family of accurate and efficient spectral methods to study a family of fractional diffusion equations and systems of fractional KdV equations [1,2,[16][17][18][19][20]. Pindza and Owolabi [21] proposed a Fourier spectral method implementation of fractional-order derivatives for reaction diffusion problems.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an immediate and natural question arises if we can get the explicit approximate solutions of time fractional WBK equations. In recent years, many powerful techniques have been extended and developed to obtain numerical and analytical solutions of fractional differential equations, such as the tau spectral method [20], the spectral collocation method [21][22][23][24], the Jacobi-Gauss-Lobatto collocation method [25], the operational matrices and spectral techniques [26] and the mesh-less boundary collocation methods [27,28].…”
Section: Introductionmentioning
confidence: 99%